How to handle stress and look after your mental health. (27th April 2009) - Iversen, Amy; Rushforth, Bruno; Forrest, Kirsty
Abstract : Junior doctors can take action to avoid stress and depression associated with their workload. This article explains how, and gives advice on who to seek help from if the need arises